ICEBs stabilised with alkali-activated fly ash as a renewed approach for green building: Exploitation of the masonry mechanical performance. (30th November 2017) - Miranda, Tiago; Silva, Rui A.; Oliveira, Daniel V.; Leitão, Dinis; Cristelo, Nuno; Oliveira, Juliana; Soares, Edgar
Highlights: The behaviour of ICEBs masonry with dry-stack and mortared joints is compared. Alkali-activated binder based earth mortars are proposed for building ICEBs masonry. ICEBs stabilised with alkali activated fly ash present slow hardening. The use of mortared joints improves the mechanical behaviour of the masonry. Contribution to the mitigation of environmental impacts. Abstract: The demand for building materials and techniques with reduced environmental impact has been increasing in the last few years. Thus, efforts have been taken to include alternative raw materials with reduced extraction impacts and low embodied energy in their production, namely natural materials and industrial by-products with low or no processing needs. Nevertheless, the lack of technical knowledge about this type of materials leads to issues related with its safety, quality and durability. The work presented in this paper intends to be a contribution on this topic. Thus, an experimental program was carried out to evaluate the mechanical performance of interlocking compressed earth blocks (ICEBs) stabilised with activated alkali fly ash. The main objective of the experimental program was to assess the possibility of further exploiting the mechanical performance of the original dry-stack masonry system, by means of the use of mortared joints. Two alkali-activated binder based earth mortars were used for this purpose, and the results showed that a substantial mechanical improvement is obtained in terms of compression and shear behaviour of the respective masonry.